Impact of industrial agglomeration on environmental efficiency of pig farming: an empirical analysis from China - Yaning Hu; Jiapeng Xu; Zhenyu Yan (International Journal of Agricultural Sustainability)
In response to environmental pressures, China’s pig farming industry has become more concentrated in regions with comparative advantages, resulting in greater agglomeration and presenting new environmental challenges. Using provincial panel data from 2005 to 2019, this study employs the Super-SBM model with undesirable outputs to measure environmental efficiency. Using the Fixed Effects Model and the Spatial Durbin Model, we examined the impact of pig farming industry agglomeration on environmental efficiency and the moderating effect of environmental regulation. Our key findings are as follows: (1) China’s pig farming industry exhibits a clear agglomeration trend of around 3.33%. (2) The intensity of environmental regulation varies across provinces and cities. (3) Environmental efficiency showed an upward trend, with the highest efficiency observed in medium-scale farms, followed by large-scale and small-scale operations. (4) There is a positive U-shaped relationship between pig farming industry agglomeration and environmental efficiency, with stronger formal environmental regulation amplifying this effect. (5) The non-linear impact of industrial agglomeration is particularly pronounced for medium- and small-scale pig farming. This study suggests that, to foster green development in pig farming and related livestock sectors, policymakers could promote moderate spatial clustering, particularly among small- and medium-sized farms, while enforcing robust formal environmental regulations.